58 THE PREVALENCE OF 4G5G POLYMORPHISM OF THE PLASMINOGEN ACTIVATOR INHIBITOR-1 (PAI-1) GENE IN POLYCYSTIC OVARIAN SYNDROME AND ITS ASSOCIATION WITH PLASMINOGEN ACTIVATOR INHIBITOR ACTIVITY LEVELS. (1st March 2005) - Glueck, C. J.; Sieve, L.; Salehi, M.; Wang, P.
Abstract : We assessed the mutant 4G allele of the plasminogen activator inhibitor-1 (PAI-1) gene in women with polycystic ovary syndrome (PCOS) and its relationship to hypofibrinolytic plasminogen activator inhibitor activity (PAI-Fx), an independent determinant of miscarriage in PCOS. We studied 913 women with PCOS who met the 2003 ESHRE/ASRM diagnostic consensus criteria and 126 healthy normal female controls. Of the 913 PCOS women, 78% had 4G4G or 4G5G genotypes vs 69% of controls (χ2 = 4.98, p = .026). The 4G allele frequency was 53% in PCOS women vs 46% in controls (χ2 = 4.06, p = .044). PCOS and normal women were both in Hardy-Weinberg equilibrium for the PAI-1 genotype distribution. By stepwise multiple regression, positive independent determinants of PAI-Fx included BMI (partial R2 = 10.8%, p<.0001), serum insulin (partial R2 = 2.7%, p<.0001), 4G4G-4G5G genotype (partial R2 = 1%, p = .0022), and triglyceride (partial R2 = 1%, p<.002); PAI-Fx was inversely associated with age (partial R2 = .5%, p = .02). Of the 913 women, 409 had previous pregnancies. By logistic regression with the dependent variable being live birth pregnancies only (n = 191), or miscarriages only (n= 69), and explanatory variables PAI-1 genotype, PAI-Fx, insulin, BMI, and triglyceride, PAI-Fx was positively associated with miscarriage, p = .017. The 4G polymorphism of the PAI-1 gene is more common in PCOS than normal women and contributes to hypofibrinolytic-miscarriage-promoting PAI-Fx levels in concert with hyperinsulinemia and hypertriglyceridemia. The 4G polymorphism of the PAI-1 gene and high PAI-Fx are markers for PCOS and its endocrine-metabolic-reproductive correlates.